Efficiency tests on gasoline engine - Stauffer, Arthur S.; Matthews, Vernon; Blair, Otis Neel (My University, 1904)
Introduction: This is a horizontal, ten horse power engine of the usual four cycle type, ignition taking place every fourth stroke and the speed being governed by cutting out charges of gasoline, (commonly called the “hit and miss" method) The following tests were made to determine the mechanical efficiency and the amount of gasoline required. The cylinder is cooled by city water direct from the hydrant. The temperatures of the cooling water were not taken as no attempt was made to determine the thermal efficiency of the engine. In the first two tests the load was applied by means of the ordinary prony brake, but as there was no provision for cooling the brake it, heated too badly for satisfactory results. In place of this was substituted a brake as shown in the frontispiece. This is a leather strap passing part way around the flywheel, the pull being recorded on a platform scale. By varying the arc of contract, the operator is enabled to maintain a steady load upon the engine.
Citation: Stauffer, Arthur S., Matthews, Vernon, and Blair, Otis Neel. Efficiency tests on gasoline engine. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Gasoline Engines; Engine Testing; Mechanical Efficiency; Theses